2009
DOI: 10.1016/j.jacc.2009.04.083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intracoronary Streptokinase Administered Immediately After Primary Percutaneous Coronary Intervention on Long-Term Left Ventricular Infarct Size, Volumes, and Function

Abstract: In this study, it has been demonstrated that low-dose ICSK given immediately after primary PCI significantly limits long-term infarct size and preserves left ventricular volumes and functions. (Effect of Complementary Intracoronary Streptokinase Administration Immediately After Primary Percutaneous Coronary Intervention on Microvascular Perfusion and Late Term Infarct Size in Patients With Acute Myocardial Infarction; NCT00302419).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 18 publications
2
36
3
Order By: Relevance
“…This evidence is relevant for potential therapeutic interventions that aim at improving the function of this part of the circulation. The present results become of special clinical relevance once it has been shown that the fibrinolysis therapy might have an additive effect to opening up larger vessels by mechanical means [17].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This evidence is relevant for potential therapeutic interventions that aim at improving the function of this part of the circulation. The present results become of special clinical relevance once it has been shown that the fibrinolysis therapy might have an additive effect to opening up larger vessels by mechanical means [17].…”
Section: Discussionmentioning
confidence: 57%
“…Thus, in addition of opening flow limiting lesions in large vessels, the cardiologist might be interested in the concomitant improvement of the microcirculation. Two recent studies are relevant in this regard [15,17]. In fact in these studies a thrombolytic agent was administered into the coronary circulation at the end of a procedure to open up the epicardial circulation so as to improve the flow in the microcirculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with anterior wall STEMI of Ͻ6 h, Stone et al (19) demonstrated that a 90-minute infusion of supersaturated oxygen into the left anterior descending coronary artery (LAD) after reperfusion significantly decreased infarct size compared with controls (18.5% vs. 25% of the left ventricle [LV]; p ϭ 0.02). Sezer et al (20) found that intracoronary streptokinase administered immediately after reperfusion reduced infarct size and LV volumes at 6 months. In a small randomized trial, high-dose erythropoietin administered during primary PCI (with repeat doses at 24 and 48 h) had no effect on convalescent LV EF assessed by magnetic resonance imaging (MRI) at 6 months (21).…”
mentioning
confidence: 99%